2015
DOI: 10.1175/jcli-d-15-0160.1
|View full text |Cite
|
Sign up to set email alerts
|

The Linkage between Upper-Level Jet Streams over East Asia and East Asian Winter Monsoon Variability

Abstract: This study investigates the linkage between East Asian winter monsoon (EAWM) variability and upper-level jets, with particular focus on the East Asian polar front jet (PJ) and its concurrent variation with the subtropical jet located to the south of the Tibetan Plateau (TSJ). The winter upper-level zonal wind variations over the Asian landmass (70°–120°E) are dominated by two principal modes (i.e., meridional displacement of the PJ and out-of-phase variation in the intensity of the TSJ and PJ) and they are clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 64 publications
3
50
2
Order By: Relevance
“…In previous studies, the strengthening of the EAWM northern mode is found to be correlated to the diminished sea ice of Arctic regions [ Luo and Zhang, ; Inoue et al, ] in recent decades. A decrease of the sea ice (warming in Arctic) tends to weaken the baroclinicity in subarctic areas and favors the cold air outbreak in northern Siberia.…”
Section: Conclusion and Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In previous studies, the strengthening of the EAWM northern mode is found to be correlated to the diminished sea ice of Arctic regions [ Luo and Zhang, ; Inoue et al, ] in recent decades. A decrease of the sea ice (warming in Arctic) tends to weaken the baroclinicity in subarctic areas and favors the cold air outbreak in northern Siberia.…”
Section: Conclusion and Discussionmentioning
confidence: 87%
“…Our model results suggest that the BC‐induced TP warming can be an alternative mechanism responsible for the strengthening of the EAWM northern mode. Recent observational studies have detected both the TP warming trend [ Duan and Xiao , ] and the intensification of the EAWM northern mode in recent decades [ Luo and Zhang, ]. These observation facts provide a support for the dynamical relationship between the TP warming and the intensification of EWAM northern mode, as identified from this study.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the northern flank of the subtropical jet, the East Asian trough remarkably deepens, characterized by an elongated belt with negative 500‐hPa geopotential height anomalies extending from central Asia to the central Pacific (Figure c). The mid‐upper tropospheric circulation anomalies favor the occurrence of cold air intrusions and, thus, an intensified EAWM circulation (Chen et al, ; Luo & Zhang, ; Zhang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the winter EAJS is associated with many synoptic-scale phenomena such as cyclogenesis, frontogenesis, blocking, storm track activity, severe snow storm, and freezing rain (Palmén and Newton, 1969;Zeng, 1979;Kung and Chan, 1981;Dole and Black, 1990;Gao and Tao, 1991;Mao et al, 2007;Liao and Zhang, 2013;Zhang and Zhang, 2013). Much effort has been devoted to the study of the intensity variability of the EAJS and its association with the East Asian winter monsoon (EAWM) in seasonal and long timescales (Yang et al, 2002;Jhun and Lee, 2004;Ding, 2005;Li and Yang, 2010;Zhang and Huang, 2011;Luo and Zhang, 2015).…”
Section: Introductionmentioning
confidence: 99%